2020
DOI: 10.1177/0020731420981856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Material and Social Deprivation on Well-Being of Elderly in Europe

Abstract: In this work, attention is paid to 2 explanatory factors of successful aging. The first is material deprivation. There is growing evidence that poverty is associated with the onset of physical and mental disorders and, broadly, with aspects such as life satisfaction and happiness. The second factor is social deprivation. Social exclusion affects health due to lack of emotional and concrete support; moreover, participation in social activities among older people is associated with greater longevity and a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…Additionally, we observed a positive association between neural vulnerability to LLD and social isolation, which was absent in participants showing neuroanatomically resilient patterns. These findings are consistent with the observations that older adults with sufficient resources to age successfully are relatively healthy, active, independent and maintain high levels of mental well-being (Terraneo, 2021), and that increases in socioeconomic status decreases the odds for depression (Freeman et al, 2016;Zhou et al, 2021). Furthermore, our results also resonate with previous findings that social isolation and/or loneliness in older adults is associated with increased risk of all-cause mortality (Holt-Lunstad et al, 2015), as well as clinically significant depression and anxiety (Schwarzbach et al, 2014;Taylor et al, 2018;Domènech-Abella et al, 2019;Donovan and Blazer, 2020).…”
Section: Discussion (312)supporting
confidence: 92%
“…Additionally, we observed a positive association between neural vulnerability to LLD and social isolation, which was absent in participants showing neuroanatomically resilient patterns. These findings are consistent with the observations that older adults with sufficient resources to age successfully are relatively healthy, active, independent and maintain high levels of mental well-being (Terraneo, 2021), and that increases in socioeconomic status decreases the odds for depression (Freeman et al, 2016;Zhou et al, 2021). Furthermore, our results also resonate with previous findings that social isolation and/or loneliness in older adults is associated with increased risk of all-cause mortality (Holt-Lunstad et al, 2015), as well as clinically significant depression and anxiety (Schwarzbach et al, 2014;Taylor et al, 2018;Domènech-Abella et al, 2019;Donovan and Blazer, 2020).…”
Section: Discussion (312)supporting
confidence: 92%
“…37,38 Social connections and emotional support may influence the social dimensions of individuals' quality of life and improve attention toward personal care. 39 A longitudinal study with older adults from England found significantly greater chances of loneliness among individuals who reported at least one oral impact on the quality of life compared to their counterparts. 40 Increasing life expectancy has resulted in populations with special oral care needs, putting additional pressure on health care systems and health funding.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators of perceived deprivation have been used to predict health-related outcomes, including perceived health status, difficulties in mobility, risks of mortality and well-being ( Myck et al, 2020 ; Terraneo, 2021 ).…”
Section: Methodsmentioning
confidence: 99%